Determination of Pollution Load Capacity Using QUAL2Kw Program on The Musi River Palembang - Lestari, Handayani; Haribowo, Riyanto; Yuliani, Emma (Civil and Environmental Science Journal (CIVENSE), 2019)
The Object of this research is a river named Musi, located in Palembang City, South of Sumatera, which is one of the longest and the biggest river in Indonesia. The condition of water quality in this river must be concerned because the high demand is not balanced with a good water quality. So, the aim of this study is to determine the value of the pollution load capacity, which is useful for consideration to government on water quality improvement policy. QUAL2Kw is used as an application to calculate the pollution capacity which entered to each river segment. There are 3 scenarios in this study, simulation 1 is calibrated model, simulation 2 is maximum of pollutant load condition, and simulation 3 is minimum of pollutant load condition. The value of pollutant load capacity is obtained from the difference between simulation 2 and simulation 3. The results show that the pollution load capacity on Musi River (particularly segment Pulokerto – PT. Baja Baru) in 2016 sequentially 12948 kgDO/day, 25205 kgBOD5/day, 3207 kg/ NH3-N day, 642 kg PO4/day